Asporin Reduces Adult Aortic Valve Interstitial Cell Mineralization Induced by Osteogenic Media and Wnt Signaling Manipulation In Vitro - Anisha Polley; Riffat Khanam; Arunima Sengupta; Santanu Chakraborty (International Journal of Cell Biology)
Worldwide, calcific aortic valve disease is one of the leading causes of morbidity and mortality among patients with cardiac abnormalities. Aortic valve mineralization and calcification are the key events of adult calcific aortic valve disease manifestation and functional insufficiency. Due to heavy mineralization and calcification, adult aortic valvular cusps show disorganized and dispersed stratification concomitant with deposition of calcific nodules with severely compromised adult valve function. Interestingly, shared gene regulatory pathways are identified between bone-forming cells and heart valve cells during development. Asporin, a small leucine-rich proteoglycan (43 kDa), acts to inhibit mineralization in periodontal ligament cells and is also detected in normal murine adult aortic valve leaflets with unknown function. Therefore, to understand the Asporin function in aortic cusp mineralization and calcification, adult avian aortic valvular interstitial cell culture system is established and osteogenesis has been induced in these cells successfully. Upon induction of osteogenesis, reduced expression of Asporin mRNA and increased expression of bone and osteogenesis markers are detected compared to cells maintained without osteogenic induction. Importantly, treatment with human recombinant Asporin protein reduces the mineralization level in osteogenic media-induced aortic valvular interstitial cells with the concomitant decreased level of Wnt/β-catenin signaling. Overall, all these data are highly indicative that Asporin might be a novel biomolecular target to treat patients of calcific aortic valve disease over current cusp replacement surgery.